Nursing and rearing of mud eel, Monopterus cuchia (Hamilton-Buchanan, 1822) with three supplementary feeds - Chakraborty, B K; Shahroz, M H; Rima, S (Journal of the Inland Fisheries Society of India, 2020)
Growth and survival of fry and fingerlings of cuchia, Monopterus cuchia was assessed in relation to three different feeds for a rearing period of 50 days. The experiment was designed with 09 plastic bowl and 30m2 (10m × 3m) cement cistern nurseries. The experiment was conducted with 03 treatments and 3 replications of each treatment designed over a period of 50 days with a stocking density of hatchery produced spawn at 0.70 million.ha-1. Treatment T1 was designed feeding with small pieces of earthworm and carp spawn, treatment T2 only with carp spawn and treatment T3 with supplementary nursery feed, respectively. Same age with a mean length and weight of 1.81±0.2 cm and 0.011±0.1 g of hatchlings was stocked in three treatments. Daily ration was adjusted three times. A significantly lower feed conversion ratio was recorded in treatment T1 followed by treatment T2 and T3. Lowest weight gain in treatment T3 and highest weight gain observed in treatment T1. Survival level was documented in the ranges of 73.00% to 90.08%, significant differences (P<0.05) was recorded among the three treatments. Similarly, the growth in terms of length (7.54±1.15 - 10.38±0.77 cm) and weight (10.11±0.82 - 13.55±1.00g) differed significantly (P<0.05) among the three treatments. But feed conversion ratio (1.00±0.03 - 1.10±0.04) did not vary significantly (P>0.05) among the treatments. The study suggested that supplying carp spawn and earthworm in treatment T1 might be advisable and supplying only carp spawn in treatment T2 may be advisable for rearing of M. cuchia fingerlings for a period of 50 days nursing. Key words Live feed; Growth; Survival; Nursery; Mud eel